2003
DOI: 10.1002/cphc.200390021
|View full text |Cite
|
Sign up to set email alerts
|

The Characterisation of Supported Platinum Nanoparticles on Carbon Used for Enantioselective Hydrogenation: A Combined Electrochemical–STM Approach

Abstract: The action of chiral modifiers like cinchonine and cinchonidine in facilitating enationselectivity in heterogeneous catalysis is investigated using a combination of electrochemical and scanning probe methods. The surface chirality of corner kink sites is suggested as being crucial for chirality recognition at supported catalyst nanoparticles. Other aspects of chirality in relation to one, two, three and four dimensions are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Those adsorbates exhibiting a lower work function than platinum tend to populate step sites in preference to terraces [6]. However, we have reported that for bismuth adsorbed on Pt{h k l}, this type of behaviour is only observed for Pt{h k l} planes vicinal to Pt{1 1 1} and that for surfaces containing more open planes, random adsorption is observed [22]. The promotional effect of various adatoms on platinum electrodes used in the electrooxidation of small organic molecules should also be noted [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 66%
“…Those adsorbates exhibiting a lower work function than platinum tend to populate step sites in preference to terraces [6]. However, we have reported that for bismuth adsorbed on Pt{h k l}, this type of behaviour is only observed for Pt{h k l} planes vicinal to Pt{1 1 1} and that for surfaces containing more open planes, random adsorption is observed [22]. The promotional effect of various adatoms on platinum electrodes used in the electrooxidation of small organic molecules should also be noted [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 66%
“…The structural attributes that determine whether or not a given chiral ligand is effective 34 have been identified; the ability to form strong covalent bonds with the metal surface while also 35 resisting hydrogenation and displacement by the strongly-adsorbing reactant under reaction conditions 36 are essential necessary conditions. Beyond these, ligand rigidity in the vicinity of the chirality center 37 coupled with resistance to SAM formation are critically important factors whose absence results in 38 racemic chemistry.…”
mentioning
confidence: 99%
“…The representative examples include the chiral reconstruction of Ni(110) induced by TA adsorption and the chiral faceting of Cu(100) upon L -lysine adsorption [13,57]. Recently, Attard et al [58] proposes the enantioselectivity of cinchona/Pt catalysts is related to the chiral kinks at the corner of catalysts nanoparticles by the combination of electrochemistry and STM observation.…”
Section: Discussionmentioning
confidence: 98%